International Initiatives Aimed at Healthy Aging Support - E. V. Burdenko (Вестник Российского экономического университета имени Г. В. Плеханова, 2025)
The article deals with the acute problem, i.e. building infrastructure to provide broader possibilities for older people. The goal of the research is to analyze designing of the healthy aging concept. Literature review on problems of infrastructure development for elderly people was carried out. Special attention was paid to age periodization of person, as it is important to define the notion of ‘older age’. Key elements of active longevity formulated by the World Health Organization were studied. It was shown that since the 1980-s international programs have been adopted aiming at attracting attention to older people problems. European countries took the lead in launching policy of active longevity. Problems arising in implementing healthy aging policy in European countries are being investigated: various health conditions in elderly people; inadequate attitude to health and pensions; outdated stereotypes (ageism); global changes. The identified problems have not been resolved jet, which resulted in developing the plan ‘The Decade of Healthy Aging for the Period 2021–2030’. Intermediate results obtained by the end of 2023 were demonstrated.